1996
DOI: 10.1063/1.117869
|View full text |Cite
|
Sign up to set email alerts
|

Microdroplet dye laser enhancing effects in dye-highly scattering intralipid mixture

Abstract: The significant effect of fat emulsion intralipid-10% mixing on lasing behaviors of liquid microdroplets was studied using rhodamine 6G dye. This highly scattering medium allows one to make the high-gain laser dye-soft scatterers microsystems that can provide well-defined lasing threshold and one-order or more magnitude enhancement of emission intensity with suitable (optimum) conditions of the mixing ratio, in comparison with original neat-dye lasing microdroplets. We also present and discuss the measured res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…2 The microcavity lasing has been studied extensively in systems of semiconductor disk, dye-doped microdroplets, and liquid jet. [3][4][5][6] A microcavity laser consisting of a fused-silica capillary filled with dye-doped liquid is an interesting system, where a coupling exists between the core WGM and the reflected light from the outer surface. Observation of interference modulation from a layered microcylinder was first performed by Knight et al 7,8 Moreover, we recently performed a precise dynamic measurement of the interference period by controlling the refractive index of the liquid continuously.…”
mentioning
confidence: 99%
“…2 The microcavity lasing has been studied extensively in systems of semiconductor disk, dye-doped microdroplets, and liquid jet. [3][4][5][6] A microcavity laser consisting of a fused-silica capillary filled with dye-doped liquid is an interesting system, where a coupling exists between the core WGM and the reflected light from the outer surface. Observation of interference modulation from a layered microcylinder was first performed by Knight et al 7,8 Moreover, we recently performed a precise dynamic measurement of the interference period by controlling the refractive index of the liquid continuously.…”
mentioning
confidence: 99%
“…Studies have reported that scattering can serve as a decisive factor for enhanced lasing in the WGM cavity. [40] With more substantial scattering, the light path inside the cavity will be longer, which in turn elongates the photon lifetime inside the cavity. The mentioned three molecules could have a similar effect inside the hydrogel cavity, resulting in a lower lasing threshold.…”
Section: Hydrogel Lasing With Different Biomoleculesmentioning
confidence: 99%
“…). This model would most appropriately describe the case of a continuous random medium such as a laser-dye doped gel or intralipid suspension 20 , where the fluctuations in η r and η i are uncorrelated. Using the Novikov theorem 23 to average over all configurations of η r and η i , we obtain in the Random Phase Approximation (RPA) (i.e., P (r, θ) = P (r)/2π),…”
mentioning
confidence: 99%